Linear Differential Equations With Analytic Coefficients of ${[P,Q]}$-Order in the Unit Disc - Latreuch, Zinelaâbidine; Belaïdi, Benharrat (Sarajevo Journal of Mathematics, 2024)
In this paper, we investigate the complex higher order linear differential equations in which the coefficients are analytic functions in the unit disc of $[p,q]$-order. We obtain several theorems about the growth and oscillation of solutions of differential equations. 2010 Mathematics Subject Classification. 34M10, 30D35